2005
DOI: 10.1002/aheh.200400568
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Chemical EPS Analyses of Activated Sludge and Scum

Abstract: The objective of this study was to quantify scum bacteria by FISH- In actinomycetes/Acinetobacter-dominated WWTP1 both lipophilic substances in the EPS and hydrophobic cell surfaces stabilized the scum layer. In "M. parvicella"-dominated WWTP2 the hydrophobic cell surfaces of these organisms were responsible for the hydrophobic sludge properties and sludge floating. In both of the selected WWTPs the detected lipophilic substances in the EPS improved growth rate and development of hydrophobic cell surfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our recent survey of 40 municipal wastewater treatment plants with scum problems which includes the WWTPs of this study revealed M. parvicella and "nocardioform actinomycetes" to be the dominant organisms in the majority of scum events (50% M. parvicella, 23% "nocardioform actinomycetes") [54]. This coincides with the high enzyme activities found in both groups pointing out their high degradation potential associated with distinct growth rates [3].…”
Section: Possible Role Of Scum Bacteriasupporting
confidence: 77%
“…Our recent survey of 40 municipal wastewater treatment plants with scum problems which includes the WWTPs of this study revealed M. parvicella and "nocardioform actinomycetes" to be the dominant organisms in the majority of scum events (50% M. parvicella, 23% "nocardioform actinomycetes") [54]. This coincides with the high enzyme activities found in both groups pointing out their high degradation potential associated with distinct growth rates [3].…”
Section: Possible Role Of Scum Bacteriasupporting
confidence: 77%
“…Classical sludge microscopy was performed according to Eikelboom [2]. Fluorescence in situ hybridization (FISH) was performed according to Amann et al [3] with slight modifications [1] with actually available oligonucleotide probes for © 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim the scum organisms mentioned above (see Table 1). Their abundance was monitored by filament index (FI) categories 0...5, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Scum biocenoses in activated sludge nutrient removal plants besides actinomycetes and "Microthrix parvicella" frequently accommodate other conspicuous organisms such as Eikelboom types 0092, 0041/0675, 0581, and 1851, as well as "Nostocoida limicola" -like organisms. In the scum fraction of high load plants often bacteria of type 1863 and non-filamentous actinomycetes are found (see Müller et al, this issue [1]). Scum bacteria have been hypothesized to contribute to sludge flotation by increasing sludge hydrophobicity and by enhancing surface active properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions have been drawn from previous studies, which used other molecular techniques, such as fluorescence in situ hybridization (FISH). For example, in a survey of 40 different WWTPs in Germany experiencing intermittent or stable foaming, Muller et al (2005) reported that nocardioform actinomycetes and Actinobacter spp. accumulated in high numbers in the foam compared with the mixed liquor fraction.…”
Section: Resultsmentioning
confidence: 99%